Metaphorical or Straightforward? Comparing the Effectiveness of Different Types of Social Media Advertising - Ding, Xin; Feng, Ping; Wang, Jingqiang; Lin, Meizhen (Frontiers in Neuroscience, 2022)
The existing studies have analyzed the advertising effects of metaphorical advertisements and straightforward adverts in traditional advertising media. However, their advertising effects in the social media are still unclear. To address this issue, our study used eye-tracking and questionnaires to examine two types of social media tourism advertising—metaphorical and straightforward in posts with both high and low popularity. This within-subject (n=55) experiment was designed to examine the effects of social media tourism advertising types on visual attention and tourism intention, and to identify the moderating role of post popularity based on the elaboration likelihood model (ELM). We found that advertising types had no significant effect on visual attention, but metaphorical advertisements increased tourism intention compared to straightforward adverts. In further, we found that the level of post popularity moderated the effect of advertising types on visual attention. Specifically, metaphorical adverts in highly popular posts attracted more visual attention in the advertising text area and in the whole advert. Straightforward adverts in posts with low popularity attracted more visual attention in the advertising text area. This research advances the current literature by exploring the effects of social media tourism advertising types and has implications for managers deciding on strategies for social media tourism marketing.